Electron-beam lithography of cinnamate polythiophene films: conductive nanorods for electronic applications [data] - Bojanowski, Maximilian; Huck, Christian; Veith, Lisa; Strunk, Karl-Philipp; Bäuerle, Rainer; Melzer, Christian; Freudenberg, Jan; Wacker, Irene; Schröder, Rasmus R.; Tegeder, Petra; Bunz, Uwe H. F. (Universität, 2022)
Research Data associated with the related publication. Synthesis and characterization of cinnamate substituted polythiophene (P3ZT). Cross linkage ...